Estrutura espacial de comunidades de anuros de duas regiões fisiográficas do bioma Pampa - Lipinski, Victor Mendes (2013)
In this study, we sampled two anuran communities in two physiographic regions of the Pampa biome, Serra do Sudeste and Depressão Central, were made monthly campaigns during the period between September 2011 and August 2012 where there were registered 25 species of frogs. Scinax granulatus, Physalaemus gracilis e Pseudis minuta were the most abundant species in the Serra do Sudeste, while Dendropsophus minutus, D. sanborni and Scinax squalirostris were the most abundant of the Depressão Central. We recorded 15 species of frogs in the larval stage and four reproductive modes classified as generalists. Ordination analysis showed a segregation among the two physiographic regions, related to anurofauna with a difference of 65% between them. The influence of environmental descriptors and physicochemical variables of water in the structure of the two communities showed that the set of variables, pH, number of extracts of emergent vegetation and temperature were important in structuring the community of Depressão Central, as dissolved oxygen, electrical conductivity number of extracts of emergent vegetation, hydroperiod and percentage of vegetation cover were important factors structuring the community of Serra do Sudeste. However the abundance and richness of the Serra do Sudeste community showed no significant relation with the variables tested and the distance between the puddles did not influence the structure of both communities.